2022
DOI: 10.3389/fmolb.2022.1031861
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of MALAT1 in respiratory diseases

Abstract: Background: The incidence of respiratory diseases and the respiratory disease mortality rate have increased in recent years. Recent studies have shown that long non-coding RNA (lncRNA) MALAT1 is involved in various respiratory diseases. In vascular endothelial and cancer cells, MALAT1 expression triggers various changes such as proinflammatory cytokine expression, cancer cell proliferation and metastasis, and increased endothelial cell permeability.Methods: In this review, we performed a relative concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…It has been reported that MALAT1 is related to cancer cell proliferation, inflammation, metastasis, fibroblast proliferation, and endothelial cell proliferation. 30 MALAT1 aggravates inflammation through modulating NF-κB and regulate airway epithelial cells to secrete IL-8 in pneumonia. 31 In our study, genes of NFKB1 and CXCL8 were expressed in MALAT1 + epithelial cells (Supplementary Fig.…”
Section: Epithelial Cells Expressed Sasp and Upregulated Inflammatory...mentioning
confidence: 99%
“…It has been reported that MALAT1 is related to cancer cell proliferation, inflammation, metastasis, fibroblast proliferation, and endothelial cell proliferation. 30 MALAT1 aggravates inflammation through modulating NF-κB and regulate airway epithelial cells to secrete IL-8 in pneumonia. 31 In our study, genes of NFKB1 and CXCL8 were expressed in MALAT1 + epithelial cells (Supplementary Fig.…”
Section: Epithelial Cells Expressed Sasp and Upregulated Inflammatory...mentioning
confidence: 99%
“…MALAT1 can worsen ALI conditions by interacting with different miRNAs [ 85 ]. MALAT1 can downregulate specific miRNAs and can ultimately facilitate the pathogenesis of ALI [ 86 ].…”
Section: Lncrnas In Ali/ardsmentioning
confidence: 99%
“…Numerous studies based on bioassays have identified changes in NEAT1 and MALAT1 expression in COVID-19 that have been associated with viral replication [ 129 , 130 ]. For example, the change in MALAT1 expression found in patients with COVID-19 was previously considered to be a regulator of the expression of a gene encoding markers of lung cancer metastasis, and its deletion led to the activation of P53 and its target genes that affect the normal cell cycle [ 131 ]. However, recent studies have shown that MALAT1 can reduce epigenetic silencing of viral transcription by regulating promoter-enhancer interaction to promote viral transcription and infection [ 132 ].…”
Section: Non-coding Rnas In Covid-19mentioning
confidence: 99%